Taḥarruš – molestowanie/napastowanie seksualne w świecie arabskim na przykładzie Egiptu. Część 1 - Nasalski, Ignacy (Studia Etnologiczne i Antropologiczne, 2017)
Group sexual harassment in the Arab World, so called taḥarruš, has reached an extraordinary extent in recent years. The problem remains unsolved despite various state actions and social initiatives. The text argues that the failure of the initiatives and information campaigns results from the fact that those actions and initiatives locate the causes outside the cultural and religious system, while it is the social structure itself, maintained by the universal nomos of religion and culture, that generates sexual frustrations which are in turn being vented in a manner combining elements of teasing and aggression. The article has been divided into two parts—the first contains a presentation of the problem, the second offers its analysis and explanation.